Fostering students’ critical thinking through literary criticisms: A student perception study - Putri Rindu Kinasih; Chesya Mapela Syalom Sitorus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Although critical thinking is an essential educational goal, it is increasingly endangered. Critical thinking can be effectively developed through literary analysis, particularly through modern theories that look at how literature interacts with psychology, historical and social contexts, and power dynamics. These modern investigations improve critical thinking skills and advance conventional literary criticism. In light of these advancements, research is being done to enhance literary criticism instruction. Unfortunately, little attention was given to how literary criticism has helped students, especially Generation Alpha, develop their critical thinking abilities. This research aims not only to understand students' perspectives regarding the literary criticism class but also how this class has influenced their way of thinking. This study adopts the mixed-method approach. The 47 participants of this study are students from the Literary Criticism of English study at Universitas Bunda Mulia, consisting of 32 female students and 15 males. This study concludes that participants generally disagree that the selected literary texts are difficult and complex. They believe that reading on a screen for extended periods of time and developing deeper comprehension are the main obstacles to comprehending literary texts, rather than a lack of English language proficiency. Combining reading and watching movies with a more direct learning activity can help with the challenge of comprehending literary texts. Lastly, this study finds that literary texts that are relevant to the participants inspire them to think, reflect, and acquire life values.